The Effectiveness of Prenatal Yoga in Reducing Anxiety and Improving Sleep Quality Among Pregnant Women A Randomized Controlled Trial - Hasibuan, Darma Afni; Siregar, Rahmi Wahida; Harahap, Meilani; Andria, Andria; Nasution, Muhammad Darwin Zulheddy; Siregar, Nurmasinar; Rangkuti, Layla Fadhilah (PT Inovasi Pratama Internasional, 2024)
Anxiety and sleep disturbances are common complications during pregnancy, affecting maternal well-being and fetal development . Prenatal yoga has emerged as a promising non-pharmacological intervention for addressing these concerns . This study aimed to evaluate the effectiveness of prenatal yoga in reducing anxiety and improving sleep quality among pregnant women through a mixed-methods randomized controlled trial. A convergent parallel mixed-methods design was employed with 120 pregnant women (20-36 weeks gestation) randomized to intervention (n=60) and control (n=60) groups . The intervention group received 8 weeks of structured prenatal yoga sessions twice weekly, while the control group received standard antenatal care . Quantitative measures included the State-Trait Anxiety Inventory (STAI) and Pittsburgh Sleep Quality Index (PSQI), assessed at baseline, 4 weeks, and 8 weeks . Qualitative data were collected through semi-structured interviews and analyzed using thematic analysis. Significant reductions in anxiety levels were observed in the yoga group compared to controls (p < 0.001) . Sleep quality improved significantly in the intervention group, with PSQI scores decreasing from 7.2 ± 1.8 to 4.1 ± 1.2 (p < 0.001) . Qualitative themes revealed enhanced emotional regulation, increased self-efficacy, and improved pregnancy experiences. Prenatal yoga is an effective intervention for reducing anxiety and improving sleep quality during pregnancy . The integration of quantitative and qualitative findings provides comprehensive evidence supporting the implementation of prenatal yoga programs in maternal healthcare services.